2009
DOI: 10.1530/eje-09-0053
|View full text |Cite
|
Sign up to set email alerts
|

D3 GH receptor polymorphism is not associated with IGF1 levels in untreated acromegaly

Abstract: Context: A discrepancy between serum GH and IGF1 concentrations is frequent in patients with acromegaly. Here, we examined whether the exon 3-deleted (d3) GH receptor (GHR) variant, which has been linked to increased responsiveness to GH treatment in short children, influences the GH/IGF1 relationship in patients with acromegaly. Objective: To study the possible influence of the GHR genotype on the GH/IGF1 relationship in untreated acromegalic patients. Design: GHR genotype analysis with retrospective clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
3
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 32 publications
3
13
3
1
Order By: Relevance
“…Serum IGF-1 levels were measured with a commercial kit, as previously reported (37). Age-adjusted IGF-1 values were calculated with age-specific reference ranges for our IGF-1 assay (IGF-1% ϭ patient's IGF-1/age specific upper limit ϫ 100, the age specific upper limit being the mean IGF-1 level normal for age and sex ϩ 2 SD).…”
Section: Hormone Assaysmentioning
confidence: 99%
“…Serum IGF-1 levels were measured with a commercial kit, as previously reported (37). Age-adjusted IGF-1 values were calculated with age-specific reference ranges for our IGF-1 assay (IGF-1% ϭ patient's IGF-1/age specific upper limit ϫ 100, the age specific upper limit being the mean IGF-1 level normal for age and sex ϩ 2 SD).…”
Section: Hormone Assaysmentioning
confidence: 99%
“…The number of patients with acromegaly examined varied from 19 to 186 among the reported series, with the prevalence of heterozygous d3/fl-GHR ranging from 13.3% to 57% and of d3-GHR homozygous from 0% to 22%. In one study, d3-GHR carriers were younger (61) and in another they had higher systolic blood pressure, fasting insulin, HOMA-IR and BMI (64). In the remaining, no clear differences in clinical parameters were observed between patients with or without d3-GHR allele.…”
Section: Ghr Polymorphism In Acromegalymentioning
confidence: 90%
“…To date, findings from 17 studies, which are summarized in Table 4, have not been consistent and the importance of the d3-GHR polymorphism in acromegaly management remains highly controversial (55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71). The number of patients with acromegaly examined varied from 19 to 186 among the reported series, with the prevalence of heterozygous d3/fl-GHR ranging from 13.3% to 57% and of d3-GHR homozygous from 0% to 22%.…”
Section: Ghr Polymorphism In Acromegalymentioning
confidence: 99%
“…Thus, to document the effects of d3 genomic variation at the GHR locus upon the acromegalic phenotype would require the observation of a large number of patients relatively homogeneous for their degree of GH excess, age range, and disease duration, conditions that are rarely met. Studies in dozens of acromegalic patients suggested that the d3 allele was (15) or was not associated with differences in GH or IGF-I levels (16,17). A larger study suggested that the d3 allele was associated with a more morbid acromegalic clinical and biochemical picture (17).…”
Section: Effects Of the D3ghr Allele In Acromegalic Patientsmentioning
confidence: 99%
“…Studies in dozens of acromegalic patients suggested that the d3 allele was (15) or was not associated with differences in GH or IGF-I levels (16,17). A larger study suggested that the d3 allele was associated with a more morbid acromegalic clinical and biochemical picture (17).…”
Section: Effects Of the D3ghr Allele In Acromegalic Patientsmentioning
confidence: 99%